2022
DOI: 10.3389/fmicb.2022.895409
|View full text |Cite
|
Sign up to set email alerts
|

Autotrophic Fe-Driven Biological Nitrogen Removal Technologies for Sustainable Wastewater Treatment

Abstract: Fe-driven biological nitrogen removal (FeBNR) has become one of the main technologies in water pollution remediation due to its economy, safety and mild reaction conditions. This paper systematically summarizes abiotic and biotic reactions in the Fe and N cycles, including nitrate/nitrite-dependent anaerobic Fe(II) oxidation (NDAFO) and anaerobic ammonium oxidation coupled with Fe(III) reduction (Feammox). The biodiversity of iron-oxidizing microorganisms for nitrate/nitrite reduction and iron-reducing microor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 116 publications
0
4
0
Order By: Relevance
“…In this study, the DO concentrations in all reactors were not higher than 0.2 mg/L, the pH levels were maintained at 6.7–7.6, and the TCOD levels were 15–80 times higher than the inhibitory threshold for Anammox bacteria, which were not suitable for the growth of nitrifying bacteria, ammonia-oxidizing archaea, or Anammox bacteria. Currently, the investigation on Feammox-related microbes is still in the infancy, but studies have suggested that IRBs (e.g., Longilinea, Bacteroides, Deltaproteobacteria, Acidobacteria, and Anaerolinea) are the primary functional bacteria mediating Feammox. ,, The relative abundances of IRBs are shown in Figure c. As shown, the total abundance of IRBs increased by 5.0–9.4% in the four Fe­(III)-supplemented reactors when compared with the control group, confirming that the addition of iron sludge could enrich the IRBs, and this was in agreement with the increased organic and NH 4 + -N removal efficiencies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the DO concentrations in all reactors were not higher than 0.2 mg/L, the pH levels were maintained at 6.7–7.6, and the TCOD levels were 15–80 times higher than the inhibitory threshold for Anammox bacteria, which were not suitable for the growth of nitrifying bacteria, ammonia-oxidizing archaea, or Anammox bacteria. Currently, the investigation on Feammox-related microbes is still in the infancy, but studies have suggested that IRBs (e.g., Longilinea, Bacteroides, Deltaproteobacteria, Acidobacteria, and Anaerolinea) are the primary functional bacteria mediating Feammox. ,, The relative abundances of IRBs are shown in Figure c. As shown, the total abundance of IRBs increased by 5.0–9.4% in the four Fe­(III)-supplemented reactors when compared with the control group, confirming that the addition of iron sludge could enrich the IRBs, and this was in agreement with the increased organic and NH 4 + -N removal efficiencies.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the investigation on Feammox-related microbes is still in the infancy, but studies have suggested that IRBs (e.g., Longilinea, Bacteroides, Deltaproteobacteria, Acidobacteria, and Anaerolinea) are the primary functional bacteria mediating Feammox. 11, 17,41 The relative abundances of IRBs are shown in Figure 5c. As shown, the total abundance of IRBs increased by 5.0−9.4% in the four Fe(III)-supplemented reactors when compared with the control group, confirming that the addition of iron sludge could enrich the IRBs, and this was in agreement with the increased organic and NH 4 + -N removal efficiencies.…”
Section: Changes Of Ironmentioning
confidence: 99%
“…Autotrophic denitrification is an alternative process for the abatement of NO 3 − and NO 2 − contaminated water [1][2][3]. It can overcome the high sludge formation problem requiring post-treatment in heterotrophic denitrification since autotrophic denitrification provides lower sludge yields [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It can overcome the high sludge formation problem requiring post-treatment in heterotrophic denitrification since autotrophic denitrification provides lower sludge yields [4,5]. Additionally, several non-toxic inorganic elements can be used as an electron donor for autotrophs, such as ferrous iron, sulphur and H 2 gas, which could lead the denitrification system to a satisfactory performance [1][2][3]. Since H 2 can be considered as an environmentally friendly substance due to its non-toxicity and non-harmfulness [6,7], using H 2 gas is a favorable option as it provides decent efficiency compared to other known electron donors for the autotrophic denitrification system [8].…”
Section: Introductionmentioning
confidence: 99%